Optimization of texture profile analysis parameters for commercial guava preserve - Antunes Vieira, Mariele; Evangelista Vasconcelos Schiass, Maria Cecília; Costa Dias, Ana Clara; Nogueira Curi, Paula; Pimenta Pereira, Patrícia Aparecida; Souza Carneiro, João De Deus; Vilela Borges, Soraia; Queiroz, Fabiana (Revista Ceres, 2025)
Motivated by the lack of studies that standardize and optimize the parameters of texture tests, this study aimed to determine the operating conditions for TPA to maximize the discrimination among samples of fruit preserves. The texture of the commercial guava preserves was evaluated using a texturometer. The Design Central Composite Rotational (DCCR) method was applied with four independent variables: speed test, sample volume, time between compression cycles and compression percentage. Only the compression percentage and test speed were significantly influenced by the texture parameters evaluated. The optimum operating region of TPA to better discriminate differences in texture parameters depended on the variable to be optimized, and for adhesiveness a compression of 75% and a compression speed of 0.23 mm·s are recommended. To detect differences among the samples for the parameters of cohesiveness, gumminess and resilience, the use of 15% compression and 2.59 mm·s speed is suggested. In both cases, one must employ the shortest time between two cycles and use a smaller sample size to save both the time of analysis and of the sample, respectively. For the parameters of hardness, elasticity and chewiness, optimal regions were not identified.